Connection between sociability and peculiarities of personal adaptation of students - N A Fomina; I V Bakova (Peoples' Friendship University of Russia (RUDN University), 2010)
This thesis is devoted to the study of correlation of variables of sociability as a system personal trait of students with peculiarities of their personal adaptation.